Rock glacier inventory of the Valles Calchaquíes Region (~ 25°S), Salta, Argentina, derived from ALOS data - Falaschi, Daniel (2014)
Rock glaciers near the Andean mountains of central and northwestern Argentina provide an important supply of water for agriculture, but data on their number, size, geographic distribution and altitudinal range are poorly known. Here, we provide the first detailed rock glacier inventory of the Valles Calchaquíes region of Salta, Argentina, based on 2.5 m x 2.5 m resolution Advanced Land Observing Satellite PRISM (Panchromatic Remote-sensing Instruments for Stereo Mapping) satellite images. Rock glacier outlines were manually digitised and a total of 488 were identified, which cover a total area of c. 59 km2. The lower limits of intact and fossil rock glaciers are at c. 4300 m asl and 4100 m asl, respectively. Because rock glaciers are protected by law in Argentina, the inventory provides an important basis for political decision-making about water resources and for further periglacial and environmental studies in this region.